2019
DOI: 10.1186/s12911-019-0888-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ICU-tailored drug-drug interaction alerts on medication prescribing and monitoring: protocol for a cluster randomized stepped-wedge trial

Abstract: Background Drug-drug interactions (DDIs) can cause patient harm. Between 46 and 90% of patients admitted to the Intensive Care Unit (ICU) are exposed to potential DDIs (pDDIs). This rate is twice as high as patients on general wards. Clinical decision support systems (CDSSs) have shown their potential to prevent pDDIs. However, the literature shows that there is considerable room for improvement of CDSSs, in particular by increasing the clinical relevance of the pDDI alerts they generate and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The alert firing rate (n=12) 43 55 62 69 70 71 72 73 74 75 76 77 and alert acceptance rate (n=15) 27 29 43 58 61 62 69 74 78 79 80 81 82 83 84 were also common metrics used to understand alarm fatigue and acceptability. Although metrics of relevance such as sensitivity, specificity, and positive predictive value (PPV) were referenced several times 77 84 85 86 87 88 , only one study evaluated these metrics as pre-specified outcomes 49 . Tools for capturing clinician burnout, stress, or satisfaction after using a CDS tool were used in nine studies 26 44 78 80 82 89 90 91 92 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alert firing rate (n=12) 43 55 62 69 70 71 72 73 74 75 76 77 and alert acceptance rate (n=15) 27 29 43 58 61 62 69 74 78 79 80 81 82 83 84 were also common metrics used to understand alarm fatigue and acceptability. Although metrics of relevance such as sensitivity, specificity, and positive predictive value (PPV) were referenced several times 77 84 85 86 87 88 , only one study evaluated these metrics as pre-specified outcomes 49 . Tools for capturing clinician burnout, stress, or satisfaction after using a CDS tool were used in nine studies 26 44 78 80 82 89 90 91 92 .…”
Section: Resultsmentioning
confidence: 99%
“…Similar to Bubp et al, expert panels were used in several studies to improve the relevance of CDS [62,71,88]. Expert panels can be advantageous over stock alerts.…”
Section: Fix It -Improving Cdsmentioning
confidence: 99%
“…However, most physicians actions over the overridden recommendations were appropriate (39). Even though a small fraction of serious DDIAs were overridden in this study, some overriding of DDIAs are acceptable in the ICU because patients are closely observed (13,44). The signi cance of these ndings is that the serious DDIAs and actionable recommendations contribute to reduce the overridden rate of DDIA in the ICU (14,45).…”
Section: -Discussionmentioning
confidence: 63%
“…Understanding drug combination use is also integral in the intensive care settings where patients are treated with many pharmaceuticals at once. It has been reported that between 46 and 90% of patients admitted to the intensive care unit (ICU) are exposed to potential drug-drug interactions [ 138 ]⁠.…”
Section: Discussionmentioning
confidence: 99%